Archetypes in architecture (1987)
ARCHETYPE, EXISTENTIAL EXPRESSION, AND SHARED EXPERIENCE Typically, first impressions of a building take the form of purely qualitative evaluations. Buildings and rooms are spontaneously characterized as 'inti- mate', 'monumental', 'dull', 'depressing', 'spartan', etc. (Fig. 2). As a rule, it is difficult to describe one's reaction. The assertion is simply made that different buildings elicit different responses. One gets an immediate sense of the whole which 'overwhelms', 'establishes a mood', and which con- cerns the architectural expression or atmosphere. One need not be ac- quainted with the building's functions, their meaning, or the distribution of rooms in order to react. In this way, an overall impression of the spirit of the building, which need not correspond to the building's function, can be quickly apprehended.